Perancangan Aplikasi Pertokoan Berbasis Desktop Pada Toko AD Jaya - Nailadea Maulana; Kiky Zulkifli (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to design a desktop-based store information system for Toko AD Jaya, which operates in the wholesale distribution of snacks and beverages. Currently, the transaction recording process is carried out manually, which is prone to errors, slows data retrieval, and complicates report preparation. This research uses a mixed-methods approach with a qualitative-dominant design, including observation, needs analysis, and system design. Quantitative data were obtained through an initial usability assessment of the system design using the System Usability Scale (SUS) instrument. By focusing on the analysis and design stages of the System Development Life Cycle and the Waterfall model, the study produces a conceptual design and system blueprint for data and transaction management. This design is expected to serve as a foundation for further application development and improve the operational effectiveness of Toko AD Jaya. Furthermore, the findings provide an initial overview of system requirements, more structured workflows, and the potential for increased accuracy and speed in business processes through digitalization.